Методология 3D моделирования при определении оптимальных характеристик алмазных кругов на этапе изготовления - Грабченко, Анатолий Иванович; Федорович, Владимир Алексеевич (Государственное образовательное учреждение высшего профессионального образования "Санкт-Петербургский институт машиностроения (ЛМЗ-ВТУЗ)", 2005)
The methodology of definition of optimum combination of strength properties of diamond grains and flow bundles at the stage of manufacturing of diamond circles and methodology of calculation of an optimum ratio of strength of flow bundle, diamond grains and their concentration is designed depending on strength properties of a worked stock.
Keywords: шлифование алмазное; зерно абразивное; состояние напряженно-деформированное; прочность